The Effect of Digital Worksheets on Dynamic Fluids with Authentic Learning in Training Problem-Solving Skills - Mustika Wati; Dwi Mugi Lestari; Saiyidah Mahtari (Jurnal Ilmiah Pendidikan Fisika, 2024)
Considering the importance of problem-solving skills in the 21st century, students should be trained in these skills, especially in sciences such as physics. Therefore, teaching materials such as worksheets are needed to train these skills. This study aims to describe the effect of digital worksheets on dynamic fluids with authentic learning in training students' problem-solving skills. The type of research used is pre-experimental with a one-group pretest-posttest design, with research subjects consisting of students in one of the XI MIPA classes in Barito Kuala Regency. The research data was collected through problem-solving skill tests before and after using the digital worksheets with the same material and then analyzed using normalized N-gain or gain scores. The results showed that the effect of the digital worksheets was in the high category with an N-gain score of 0.75, and students reached a good category in problem-solving skills. Therefore, it can be concluded that the digital worksheets on dynamic fluids with authentic learning effectively train students' problem-solving skills and can be used as input for teachers to train students' problem-solving skills.